Influence of interleukin 10 polymorphisms -592 and -1082 to the HIV, HBV and HCV serostatus among intravenous drug users. - Kallas, Eveli; Huik, Kristi; Pauskar, Merit; Jõgeda, Ene-Ly; Karki, Tõnis; Jarlais, Don Des; Uusküla, Anneli; Avi, Radko; Lutsar, Irja (Infection, genetics and evolution : journal of molecular epidemiology and evolutionary genetics in infectious diseases, 2014)
Interleukin 10 (IL-10) is a multifunctional cytokine produced by macrophages, monocytes, and T-helper cells. Two polymorphisms at positions -592 and -1082 have been associated with HIV susceptibility. However, their associations with susceptibility to HIV and its co-infections among intravenous drug users (IDUs) are largely unknown.